The Role of Sexual Reproductive Health Awareness in Reducing HIV Infections Among the Youth in Kibaha District, Tanzania (Tanzania Journal for Population studies and Development, 2020)
This article assesses the role of sexual reproductive health awareness in reducing HIV infections among the youth in Kibaha District, Tanzania. The objective is to investigate the role of sexual reproductive health awareness in reducing HIV infections among the youth. The study results revealed that more mature youth were more aware of the pandemic, while gender-wise females were more aware than males. Moreover, married couples were more aware because of their direct involvement in reproduction; and those involved in business were more aware of the pandemic due to high mobility. In terms of land ownership, youth with land were more informed than those who were landless, and youth who earned higher income were more aware than those with less income. There were no significant differentials in awareness between religions. The results on other socioeconomic variables indicated that people who had more access to mass media, like radios, were more aware of the pandemic, as were those with modern houses. Moreover, youth who used electricity as a source of energy were more aware than those who used other sources of energy like firewood. The desire for money and other materials was the major driving force for youth getting HIV infections. Also, heterosexual sex was the major means of HIV transmission, and the major forums where youth got information on the pandemic were youth groups in the community from health centres. The study recommends that efforts of controlling the pandemic be stepped up, and more posters be put in transit routes to warn the community of the pandemic.